The growth-employment-poverty nexus in Latin America in the 2000s: Chile Country Study - Cruces, Guillermo Antonio (2015)
During the 2000s Chile achieved rapid economic growth and improved most labour market indicators: the unemployment rate fell; the mix of employment by occupational position and sector improved; the educational level of the employed population, the percentage of registered workers, and labour earnings increased; and all poverty and inequality indicators decreased. The economy suffered a recession during the international crisis of 2008, but recovered quickly. Some labour market indicators were negatively affected by the crisis. The unemployment rate was the only indicator that did not return to its pre-crisis level by the end of the period studied.